Characterization and Immunogenicity of a Novel Mosaic M HIV-1 gp140 Trimer - Nkolola, Joseph P. (American Society for Microbiology, 2014)
The extraordinary diversity of the human immunodeficiency virus type 1 (HIV-1) envelope (Env) glycoprotein poses a major challenge for the development of an HIV-1 vaccine. One strategy to circumvent this problem utilizes bioinformatically optimized mosaic antigens. However, mosaic Env proteins expressed as trimers have not been previously evaluated for their stability, antigenicity, and immunogenicity. Here, we report the production and characterization of a stable HIV-1 mosaic M gp140 Env trimer. The mosaic M trimer bound CD4 as well as multiple broadly neutralizing monoclonal antibodies, and biophysical characterization suggested substantial stability. The mosaic M trimer elicited higher neutralizing antibody (nAb) titers against clade B viruses than a previously described clade C (C97ZA.012) gp140 trimer in guinea pigs, whereas the clade C trimer elicited higher nAb titers than the mosaic M trimer against clade A and C viruses. A mixture of the clade C and mosaic M trimers elicited nAb responses that were comparable to the better component of the mixture for each virus tested. These data suggest that combinations of relatively small numbers of immunologically complementary Env trimers may improve nAb responses. IMPORTANCE The development of an HIV-1 vaccine remains a formidable challenge due to multiple circulating strains of HIV-1 worldwide. This study describes a candidate HIV-1 Env protein vaccine whose sequence has been designed by computational methods to address HIV-1 diversity. The characteristics and immunogenicity of this Env protein, both alone and mixed together with a clade C Env protein vaccine, are described.